If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + 9x = 0 Solving 24 + 9x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 9x = 0 + -24 Combine like terms: 24 + -24 = 0 0 + 9x = 0 + -24 9x = 0 + -24 Combine like terms: 0 + -24 = -24 9x = -24 Divide each side by '9'. x = -2.666666667 Simplifying x = -2.666666667
| 76=2n-30 | | (5x-3)(6x-7)= | | -3x-4-5=-36 | | 76=253-30 | | -4(x-3)=-4(3-x) | | 75+.10x=200+.05x | | 2/10×=20/1 | | 45-81/9 | | 3x-2=1/3 | | 3x-3=1/3 | | x(squared)-16= | | 3x+37=86 | | 5x-2y=13forx | | 6x+2y=47 | | (r^2)+4=-4r-19 | | 7x(3x/4) | | (4a-3)(2a+7)= | | 30w-(-w+6)+a(-5w+4)=-(5w+6)+(-8+3w) | | -6x+12+12-24=-36 | | 23x-14x+7=61 | | d=iqx | | y=3/2-1 | | 8x-3+6x=7x+5-9x | | .25x-35=50 | | 2x+2x+2=8x-14 | | 0=-2.5x+80 | | 21x+15-13x=-73 | | -n+8n=5n | | 9x+6x=195 | | 5(d+2)=3(d+-6) | | 2/5w | | 14+2x+6=24 |